Contents Vol 30 No 2 2023 - Septorini Wimardhani, Dr. Yuniardini Septorini (UI Scholars Hub, 2023)
This is the contents of the 2nd number of the Volume 30 December 2023 edition of the Journal of Dentistry Indonesia.